Bureaucracies of Blood and Belonging: Documents, HIV‐positive Youth and the State in South Africa. Issue 6 (27th September 2017) - Vale, Beth; Hodes, Rebecca; Cluver, Lucie; Thabeng, Mildred
ABSTRACT: In response to its constitutional commitments and social welfare provisions in the era of democracy, the post‐apartheid South African state is increasingly called upon to provide for the lives and livelihoods of its citizens. These demands have intensified amid escalating joblessness and the highest numbers of people living with HIV worldwide. Over the past decade, antiretroviral treatment (ART) has been incorporated into an ever‐expanding welfare bureaucracy, in which access to state assistance is mediated by the collection and monitoring of biometric, bureaucratic data. Drawing on 18 months of ethnographic research in the Eastern Cape, this article explores how state documents bring young people on ART into an ambiguous relationship with the state — one that is at once subordinating and enabling. While social research on ART addresses both the empowering and coercive aspects of treatment taking, less attention has been given to how these modes of participation might be mutually constitutive. In this article, the authors examine how the same technologies that discipline youth on ART might also support and protect them; how welfare dependencies entail paradoxical forms of agency; and how the state's ability to control and to 'care for' citizens might be reciprocally dependent.